2014
DOI: 10.1038/bjc.2014.172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and oesophageal squamous cell carcinoma: a systematic review and meta-analysis

Abstract: Background/Objective:Dietary patterns, which represent a complex integration of food and nutrients, have been used to explore the association between dietary factors and the risk of oesophageal cancer. However, the association remains unclear. This systematic review was performed to evaluate the relationship between dietary patterns and oesophageal squamous cell carcinoma (ESCC) by pooling available data from existing studies.Methods:Pertinent articles published up to the end of 2013 were systematically search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 47 publications
7
32
2
Order By: Relevance
“…Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45]. On the other hand, no significant correlation was evidenced for breast [42], rectal and esophagus cancers [43,46]. The Western pattern identified in the present investigation, likewise reported in the above reported meta-analysis, is characterized by high consumption of red meat, processed meat, eggs and sweets.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45]. On the other hand, no significant correlation was evidenced for breast [42], rectal and esophagus cancers [43,46]. The Western pattern identified in the present investigation, likewise reported in the above reported meta-analysis, is characterized by high consumption of red meat, processed meat, eggs and sweets.…”
Section: Discussionsupporting
confidence: 90%
“…Several systematic reviews and meta-analysis have recently reported the association between dietary patterns and risk of cancer in different sites such as breast [42], colon and rectum [43,44], stomach [45], esophagus and lung [46,47]. Similar to our results, in some meta-analysis it was found that the consumption of a Western dietary pattern was positively associated to an increment of cancer risk in the colon [43], colorectal and stomach [44,45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies have shown that in countries with medium HDI, EC is one of the most common cancers . Indeed, EC is more common in less developed or developing countries due to smoking, alcohol consumption, nutritional status, environmental pollution and life style behavior (Keramatinia et al, 2016;Koca et al, 2015;Liu et al, 2014;Napier et al, 2014;Wang et al, 2015) -combine. HDI is moderate or low in areas with high rates of EC.…”
Section: Discussionmentioning
confidence: 99%
“…EC is one of the cancers that are strongly associated with social and economic status (Dar et al, 2013;Wang et al, 2015). Studies have shown that tobacco, weak nutrition and alcohol are most associated with EC, especially the SCC type (Lin et al, 2013;Liu et al, 2014;Salehi et al, 2013). Furthermore, low income populations have a higher chance of mortality from EC because they have less access to prevention and treatment services (Wang et al, 2013;Wei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%